2013
DOI: 10.1680/wama.11.00040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sorption process on cadmium transport

Abstract: The effect of sorption of cadmium to sediments is investigated through an experimental and numerical study. A numerical model is developed to evaluate the kinetic and equilibrium sorption process of heavy metal transport and transformation. The model was calibrated with results from experiments on cadmium and salt injection in a circular flume. The effect of sediment on sorption was then investigated by the aid of advection-dispersion experiments and numerical results. The results show that sorption reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…where, C0 is the initial cadmium concentration (t = 0) and C is the cadmium concentration at different times (ppb), Ɐ is the volume of the water (130 lit), and W is the weight of the sediments (gr). For the kinetic modeling, a pseudo second order equation is used (Ho and McKay 1999;Azizian 2004;and Mahdavi et al 2013), as follows:…”
Section: Figure 1 About Herementioning
confidence: 99%
“…where, C0 is the initial cadmium concentration (t = 0) and C is the cadmium concentration at different times (ppb), Ɐ is the volume of the water (130 lit), and W is the weight of the sediments (gr). For the kinetic modeling, a pseudo second order equation is used (Ho and McKay 1999;Azizian 2004;and Mahdavi et al 2013), as follows:…”
Section: Figure 1 About Herementioning
confidence: 99%
“…Ng (2000), Wu et al (2005) and Mahdavi et al (2009) concluded that phase exchange, including adsorption and detachment, would occur between both parts, indicating the significant role of sediment particles in transport transformation processes. As an example, in experimental work conducted by Mahdavi et al (2012), it was observed that the presence of bed load materials would result in a 20% decrease in dispersion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, in TST experiments the advection parameter, which is a key factor in sediment and pollutant transport, is ignored; consequently, this technique does not offer a fair simulation of the natural conditions. In this regard, Mahdavi et al (2009Mahdavi et al ( , 2012 proposed a circular flume to better simulate natural conditions. This work paved a path towards a comparison of results taken from reactors and natural rivers with bed load movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment transport also plays an important role in pollutant transport. Mahdavi et al (2013) investigate sorption of cadmium in sediment, transport of cadmium with sediment and desorption back into the water. An experimental setup with a circular flume simulating river flow was applied for modelling adsorption of cadmium in sediment.…”
mentioning
confidence: 99%